Non-covalent functionalization of multi-wall carbon nanotubes with polyarginine: Characterization and analytical applications for uric acid quantification - Gutierrez, Alejandro (2018)
We report for the first time the non-covalent functionalization of multiwall carbon nanotubes (MWCNTs) with polyarginine (Polyarg), the modification of glassy carbon electrodes (GCE) with the resulting Polyarg-MWCNTs dispersion and the analytical application of Polyarg-MWCNTs-modified GCE for the quantification of uric acid. The optimum MWCNT-Polyarg dispersion was obtained by sonicating for 5.0 min the mixture of 0.75 mg mL−1 MWCNTs and 0.50 mg mL−1 Polyarg. The dispersion was characterized by scanning electron microscopy, electrophoretic mobility, electrochemical impedance spectroscopy, cyclic voltammetry and amperometry. The presence of MWCNT-Polyarg at GCE surface produced a drastic decrease in the overvoltages for the oxidation of hydrogen peroxide (300 mV) ascorbic acid (281 mV) and uric acid (70 mV) and for the reduction of hydrogen peroxide (200 mV), as well as an important decrease in the charge transfer resistances for hydrogen peroxide, hydroquinone/quinone and ferricyanide/ferrocyanide markers. The strong adsorption of uric acid at GCE/MWCNT-Polyarg made possible the highly sensitive detection of this biomarker at nanomolar levels even in the presence of 1.0×10−4 M ascorbic acid by Adsorptive Stripping with medium exchange and linear scan voltammetry transduction. The quantification of uric acid in untreated human urine was very successful, demonstrating an excellent correlation (98 %) with the reference method used in clinical laboratories (Uricostat, Wiener Lab).